CALLUS INDUCTION AND DIRECT ORGANOGENESIS IN SAFFRON CALLUS BY USING PLANT EXTRACT AS AN ALTERNATIVE TO PHYTOHORMONES - Jalal, Junaid; Manzoor, Usma; Ahmad, Tanweer; Chowdery, Rukaya A.; Mir, Raouf Ahmad (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
Objectives: Saffron (Crocus sativus) is mostly propagated vegetatively. Therefore, cost-effective methods need to be developed, in order to multiply and increase the yield of saffron. The aim of present study was to use plant extract as an alternative to phytohormones for regeneration of saffron corms in in-vitro conditions. Methods: Tiny slices or fragments of saffron corms were used as explants and cultured on Murashige and Skoog (MS) media supplemented with plant extract to obtain the callus. Results: Callus initiation was observed in all concentrations of plant extract. However, the callus grown in 20% plant extract resulted in direct organogenesis. But callus growth was slow at 40% concentration of plant extract. Conclusion: Our results showed that plant extract can be used as an efficient alternative source to phyto- hormones. Â